2016
DOI: 10.1038/jp.2016.123
|View full text |Cite
|
Sign up to set email alerts
|

Health-care provider communication with expectant parents during a prenatal diagnosis: an integrative review

Abstract: The pregnancy and health-care experience of expectant parents who receive a prenatal diagnosis of their unborn infant is distinctively fraught with uncertainty. Health-care providers (HCPs) that care for parents during this uncertain time have an exceptional opportunity to positively impact parental outcomes. An integrative literature review was conducted to explore HCPs' impact on parents' experiences of receiving a prenatal diagnosis. Thirty-three articles met study inclusion criteria (n=18 qualitative; 6 qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 56 publications
4
39
0
Order By: Relevance
“…Our findings converge with three reviews addressing experiences of prenatal diagnosis more broadly. Our findings regarding parents' needs concur with results from an integrative review into mothers' experiences of prenatal diagnoses which found that HCPs' communication skills helped them cope 13 . Our results also converge with a review of qualitative studies into experiences of lethal prenatal diagnoses, which suggested that parents valued timely, written information about the diagnosis 14 .…”
Section: Discussionsupporting
confidence: 82%
“…Our findings converge with three reviews addressing experiences of prenatal diagnosis more broadly. Our findings regarding parents' needs concur with results from an integrative review into mothers' experiences of prenatal diagnoses which found that HCPs' communication skills helped them cope 13 . Our results also converge with a review of qualitative studies into experiences of lethal prenatal diagnoses, which suggested that parents valued timely, written information about the diagnosis 14 .…”
Section: Discussionsupporting
confidence: 82%
“…In the context of sometimes rapid developments in the diagnosis and treatment of fetal health conditions, communication has been found to vary significantly: from the role of the clinician providing the counseling to the training they have or have not received, all of which varies from institution to institution. 1 The difference between not recommending ECMO in prenatal counseling for a child with minimal lung volume and no diaphragm and explicitly recommending some resuscitative measures, even a short ventilator trial, or comfort care are important. In my clinical practice, I had concerns about how the conditions of parental decision-making are shaped by clinicians.…”
Section: In Practicementioning
confidence: 99%
“…Additionally, current prenatal home visiting programs are focused on the needs of families with environmental risks, such as low income and/or adolescent parents, which may not be structured or readied to address family needs unique to experiencing diagnoses with a high probability of developmental delay and disability, which is the intent of Part C EI. For example, prior prenatal research found that families were in need of accurate and current information to then process the diagnosis and its implications on child development and family life, provided in a hopeful manner (Hickerton et al 2012;Kratovil & Julion 2017;McKechnie et al 2015;Roscigno et al 2012). EI professionals are prepared to provide such diagnosis-specific supports.…”
Section: Prenatal Supports In National Policymentioning
confidence: 99%
“…Families reported needing a balance of individual time to process the diagnosis while keeping in contact with extended family and friends as their personal support system, as well as connecting with other families who have a child with the same diagnosis and community-based resources available to meet the family's priorities (Hickerton et al 2012;McKechnie et al 2015). Recommended emotional supports focus on sharing a positive and hopeful perspective that the family can meet their prenatal and parenting goals and vision, including whether or how to undertake typical prenatal rituals with others, such as baby showers, pregnancy announcements, or documenting and sharing the pregnancy (Kratovil and Julion 2017;McKechnie et al 2015;Roscigno et al 2012). In a review of the literature on family preferences for receiving and understanding a prenatal diagnosis, Kratovil and Julion (2017) found that the type and amount of information families (mostly mothers in the studies) wanted from their healthcare providers were distinct for each family and cautioned that providing too much or too little than the family desired could increase anxiety.…”
Section: Focus Of Part C Ei As a Family Support Programmentioning
confidence: 99%
See 1 more Smart Citation